Micro-tube fabricating path compensation method research. Issue 9 (August 2016) - Gong, Youping; Lv, Yunpeng; Su, Shaohui; Li, Zhihua; Chen, Guojin
Abstract Inkjet printing approach has been applied to fabricate various biological constructs, such as alginate tubes. During the printing, the possible buckling due to the self-weight and the impact force induced by the droplet deposition needs to be taken into consideration. The paper aims to investigate how to theoretically construct a predicted tube printing path which can compensate for deformation in the printing process. Firstly, a nonlinear deflection model is proposed to estimate the critical tube diameter for a fixed droplet impaction where the printed tube is simplified to be a curved beam where one end is fixed and the other end is a free end and puts forward the predicted-path algorithm of the tube fabrication based on the model. Secondly, numerical simulation method is used to verify the effectiveness and correctness, The max errors between the theory method and numerical test are not more than 15 μm, thus supporting the theoretical results existing in the literature. Lastly, a predicted path was adopted to print the tube, obtained a more tube-shaped structure, and the cross-section of the fabricated constructs can be nearly circular with the predictive compensation path.